Efecto de la vacunación de pollos de engorde contra Mycoplasma gallisepticum (MG) (1989)
Experimental vaccination via eye drop with "F" strain of the Mycoplasma gallisepticum (MG) of 200 one day old commercial broilers divided in four groups of 50 chicks each, resulted in better body weigth better feed conversion and less number of air sac lesions when were compared with the unvaccinated group, but challenged 10 contac infected chickens with "R" strain of the MG, to simulated egg transmission.